Good for you : bold flavors with benefits : 100 recipes for gluten-free, dairy-free, vegetarian, and vegan diets - Nawab, Akhtar; Strong, Andrea (Chronicle Books, 2020)
"GOOD FOR YOU is a cookbook that infuses clean eating with rich flavor. Inspired by his Indian heritage, Kentucky upbringing, and professional experience cooking in Mexican and Italian restaurants, Akhtar Nawab presents 100 healthful recipes that satisfy every appetite. From basic building blocks--like vegan soubise and gluten-free bread--to recipes like Blueberry Ginger Smoothie, Gazpacho with Poached Shrimp, Fish Tacos with Pistachio Mole, and Dark Chocolate Almond Butter Cups with Sea Salt, this book is for anyone who wants to eat well and feel good. With bright, enticing photography, GOOD FOR YOU will attract both amateur and seasoned home cooks interested in wholesome, accessible recipes that pack serious flavor into every bite"--